Digitalization Strategy of Greenhouse-Based Fruit Picking Tourism Through Green Marketing Platform Integration of Social Customer Relationship Management as Economic Strengthening of Premium Fruit Farmer Groups - Wulandari, Dwi; Prasetyo, Abdul Rahman; Prayitno, Putra Hilmi; Basuki, Andi; Gunawan, Ari; Syaifruddin, Afis Baghiz; Wulandari, Widia Ayu (Global Writing Academica Researching and Publishing, 2025)
Sustainable agriculture currently faces many challenges, including the weak bargaining position of premium fruit farmers, limited direct market access, and a lack of innovative agricultural tourism innovation. On the other hand, the shift in public interest towards experience-based tourism and environmental issues has opened up new opportunities for integrating agrotourism with greenhouse-based practices. The purpose of this study is to investigate the strategy of strengthening premium fruit farmers by utilising the greenhouse-based fruit-picking tourism method, supported by digital technology and principles of the green economy. Quantitative descriptive methods were used to collect data in two locations, Kediri and Ponorogo, through observation, interviews, and statistical documentation. The number of tourist visitors, digital transactions, social media engagement, premium fruit sales volume, and garden harvest capacity, both before and after the program implementation, were the indicators analysed. All indicators have increased significantly, according to the research results. Tourists increased by 121.4% in Kediri and 94.4% in Ponorogo. These data show that the park-based tourism model not only increases the productivity and marketability of agricultural products but also creates a digital ecosystem that expands market access and strengthens farmer branding. The role of digital technology in this success story should inform the audience about its potential in the agricultural sector. Premium fruit sales volume increased by 68.6%, while audience engagement through social media increased by 246%, and garden harvest capacity increased by 84%. Therefore, this approach has proven effective in encouraging the transformation of farmers' roles into adaptive agro-digital entrepreneurs. This study recommends applying this model in other regions to foster inclusive and sustainable agriculture through the support of training, digital infrastructure, and multi-party cooperation.